2017
DOI: 10.3354/meps12158
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal occurrence of killer whale ecotypes off the outer coast of Washington State, USA

Abstract: Three killer whale Orcinus orca ecotypes inhabit the northeastern Pacific: residents, transients, and offshores. To investigate intraspecific differences in spatial and temporal occurrence off the outer coast of Washington State, USA, 2 long-term acoustic recorders were deployed from July 2004 to August 2013: one off the continental shelf in Quinault Canyon (QC) and the other on the shelf, off Cape Elizabeth (CE). Acoustic encounters containing pulsed calls were analyzed for call types attributable to specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 28 publications
2
20
2
Order By: Relevance
“…5). Also, previous studies have shown that K and L pods are typically absent from their usual summertime areas during December− May (Ford 2006), and seem to make use of outer coast areas like Swiftsure (as in the present study) and waters from Washington down to California (Hanson et al 2013, Rice et al 2017. Although monitoring at all of these outer coast sites during the winter months has resulted in relatively low rates of encounter compared to summertime encounter rates in critical habitat, taken collectively this suggests that Southern Residents range widely in the winter and rely on the shelf waters of this outer coast region in its entirety in the wintertime.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…5). Also, previous studies have shown that K and L pods are typically absent from their usual summertime areas during December− May (Ford 2006), and seem to make use of outer coast areas like Swiftsure (as in the present study) and waters from Washington down to California (Hanson et al 2013, Rice et al 2017. Although monitoring at all of these outer coast sites during the winter months has resulted in relatively low rates of encounter compared to summertime encounter rates in critical habitat, taken collectively this suggests that Southern Residents range widely in the winter and rely on the shelf waters of this outer coast region in its entirety in the wintertime.…”
Section: Discussionsupporting
confidence: 66%
“…Similar to Southern Residents, it could be that Northern Residents are exploiting early Chinook runs that appear in the area as the fish migrate towards their natal rivers. Southern Residents have been detected near the mouth of the Columbia River between January and May, and also around Cape Elizabeth, just north of the Columbia River, between January and June (Rice et al 2017), timing that coincides with the return of spring Chinook to the Columbia River (Hanson et al 2013). Also, juvenile Chinook salmon can be found off the west coast of Vancouver Island during all seasons (Tucker et al 2012), suggesting they may find adequate conditions and food supply in highly productive areas such as Swiftsure Bank and exploit these locations during the winter as adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many areas, visual monitoring is limited and cost prohibitive due to protracted periods of inclement weather, remote access, and short daylight hours. In these locations, remote acoustic monitoring is an effective alternative for vocally active species such as killer whales which produce discrete pulsed calls, whistles, and echolocations clicks (Schevill & Watkins 1966, Hanson et al 2013, Rice et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Critical habitat was designated for SRKW in the inland waters of Washington State in 2006 (NMFS 2006), but the whales typically only spend a fraction of the year in these waters (Olson et al 2018). Passive acoustic monitoring (PAM) has been used at selected sites along the west coasts of Washington, Oregon, and California to better understand SRKW movements outside of the inland waters, especially during winter months (Hanson et al 2013, Rice et al 2017, and has led in part to the proposed expansion of critical habitat to include these waters (NMFS 2019).…”
Section: Introductionmentioning
confidence: 99%